(untitled) (American Journal of Arts and Human Science, 2024)
Attempts at regionalization and integration are increasingly viewed as offering chances for guaranteeing peace, stability, and sustained economic growth in the face of Africa’s numerous security concerns. As a result, organizations dedicated to regional integration and cooperation, like EAC, are beginning to take on the role of conflict resolution experts in their particular areas. Therefore, this study’s primary goal was to evaluate how regional integration contributes to African peace and security. In particular, the study was conducted to determine the various missions that EAC members carried out to restore peace and security in member nations, as well as to assess the effects of various policies created by the EAC to address peace and security concerns among member states. Furthermore, this study exclusively used secondary data. From online books, articles, reports, conference papers, magazines other research papers and assess the effects of the various policies that the East Asian Community (EAC) established to address issues of peace and security among its member states. Additionally, the missions that the EAC members carried out to help member states that needed to regain peace and security and were affiliated with the East were reviewed. Furthermore, it was discovered that regional integration had the subsequent implications for security and peace: strengthened domestic peacekeeping forces by means of regional collaboration; provided members with monetary assistance to sustain peace and security; and made it simple to obtain support and assistance from non-member nations in emergency situations. East Africa is now united as a result of the EAC’s formation. But the EAC still has certain obstacles to the advancement of peace and security as well as regional integration. For instance, it was discovered that certain states are not fully dedicated to regional peace and security strategies, and it was also mentioned that a shortage of resources and training is one of the challenges to implementing peace. for these reasons I would recommend that members states pay on time their contribution, members states should be committed to the agenda of the community a finally, states should resolve conflicts between and among themselves.